A dynamic gear load distribution model for epicyclic gear sets with a structurally compliant planet carrier. (March 2023) - Ryali, Lokaditya; Talbot, David
Highlights: Efficient contact model for planetary gears, with carrier and shaft compliance included. Gear mesh load distribution can become heavily skewed, due to carrier deformations. Additional compliance due to carrier flexibility improves load sharing among planet branches. Significant change in the dynamic response is observed due to inclusion of carrier flexibility. Abstract: Structural deformations in a planet carrier under operating conditions results in misalignment of planet gears, which can significantly effect the gear mesh load distribution and load sharing of a planetary gear set. Therefore, to capture the influence of structural compliance associated with planet carrier, planet pin, and input/output shaft, a hybrid planetary dynamic load distribution model is developed in this paper. Finite element sub-structuring techniques are employed to ensure that the model is computational efficiency. The proposed model employs a simplex algorithm to iteratively solve for the elastic gear mesh contacts in conjunction with a numerical integration scheme, which enables it to inherently capture the influence of several component and system level design variations without the need for an empirical mesh stiffness formulation or transmission error excitation of the system. The developed formulation is used to study the effects of planet carrier flexibility on both the quasi-static and dynamic response of planetary gearsets. The discussed results not only illustrate the influence of carrier flexibility on the system response but also highlight the need for such computationally efficient models which could be used as design tools.